Surgical Management of Falcotentorial Junction Tumors: A Case Series Report - Liu, Peixi; Wang, Xiaowen; Liu, Yingjun; Cai, Jiajun; Yang, Zixiao; Quan, Kai; Zhu, Wei; Song, Jianping (Frontiers in Oncology, 2022)
Objective The surgical strategy for falcotentorial junction tumors remains complex. Different approaches are selected according to the location and growth pattern of the tumor and the operator’s experience. This report reviews our single-institution experience in the surgical management of falcotentorial junction tumors. Methods We retrospectively reviewed the clinical and imaging data, surgical strategy, and follow-up outcomes of 49 patients treated from 2007 to 2020. Result All 49 patients (12 male, 37 female, mean age: 56.3 ± 11.3 years) underwent safe tumor resection. The most common complaints were headache (43%), dizziness (39%), and unstable gait (16%). Thirty percent of the tumors showed calcification, and the computed tomography scans revealed hydrocephalus in 36% of the patients. On magnetic resonance imaging, 43% of the tumors were unilateral. According to the Asari classification, the tumors were divided into inferior (16%), superior (29%), anterior (22%), and posterior (33%) types. The occipital interhemispheric approach (88%) and supracerebellar–infratentorial approach (10%) were primarily used to reach the tumors. The pathology examination results revealed that 85.7% of the tumors were meningioma and 14.3% were hemangiopericytoma. Of the 49 patients, 15 achieved a Simpson grade I resection, and 29 achieved a Simpson grade II resection. The follow-up rate was 77.6% (38/45); 94.7% of patients (36/38) achieved a favorable outcome, and 9 experienced tumor recurrences. Conclusion Surgical approach selection depends on the growth characteristics of the tumor and the degree of venous or sinus involvement. The occipital interhemispheric approach is the most commonly used and safest approach for falcotentorial junction tumors with multiple brain pressure control assistance techniques.